DEVELOPMENT OF MULK WINE TECHNOLOGY - SAMILYK, MARYNA; NOSYK, MYKOLA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents the technology of wine production from mulberry fruit. A feature of the proposed technology is the use of osmotic dehydration for preliminary dehydration of mulberry. The solution formed as a result of osmotic dehydration is proposed to be introduced into the must during fermentation.Organoleptic and physicochemical parameters of the wine were determined by standard methods. Mórus nígra L. fruit were dehydrated in a 70% sucrose solution for 1 hour at a temperature of 50±5°C. The wine mixture was prepared from the must (100%), the spent osmotic solution (50%) and the juice formed during the pressing of partially dehydrated mulberry fruits (50%). Slow fermentation of the mixture was carried out for 4 days at a temperature of 20±2 °C under static conditions. At the stage of active fermentation, 10% of the osmotic solution was introduced into the fermenter in several stages. The addition of an osmotic solution increases the density of the wine and the sugar content. The density (1.049±0.05 g/cm3) and the mass fraction of sugars (106.95±0.05 g/dm³) of mulberry wine are higher than those of grape wine. The high sugar content (10.1±0.05%) gives the wine a sweet and rich taste, and also contributes to the stability of the wine during storage after opening the container. The mulberry wine had a more saturated color (T=0.814±0.05) and a higher color intensity (9.98±0.05), typical of aged wines. The high color intensity is associated with the high content of phytochemicals produced in the wine. The highest optical density (0.491±0.05 D) of mulberry wine is observed at a wavelength of 520 nm, i.e., in the red range, which indicates a high content of anthocyanins. Wine made from mulberry fruit processing products had a pleasant taste and color. The light taste of the wine indicated a low alcohol content. Mulberry wine can be classified as semi-dry, since it has a low alcohol content (6±0.5%).
Keywords: mulberry fruit; wine technology; osmotic dehydration; organoleptic characteristics; physicochemical parameters